2-Dimensional Resistivity Imaging of Inyi Coal-Field, Anambra Basin, Nigeria - Chukwudi Chris Ezeh; Ujunwa Angel Oti; Ayatu Ojonugwa Usman; Austin Chukwuemeka Okonkwo (Newinera Publisher, 2021)
2-Dimensional resistivity imaging of Inyi coalfield has been carried out with a view of imaging the coal field for possible location and future exploitation of the coal seam in the area and to carry out detailed geological mapping aimed at producing the geologic map of the area and to provide recommendations for managing the exploitation and exploration of solid minerals in the area. ABEM Terrameter SAS 1000 was used for resistivity data collection and Wenner-Schlumberger array electrode configuration was used because of its sensitivity to both horizontal and vertical structures. 2-D imaging was targeted at determining the lateral extent of the coal seam, the depth to the coal seam and the thickness of the coal seam. 50 VES points was conducted to help in delineating lithology and to be used in correlating 2-D results. Result reveals a resistivity values ranging from 600Ωm to 45000Ωm around the surveyed area. It also show that the coal in the area occurred at varying depth between 4m to about 14.3m which could be extensive below this depth and the thickness ranging from 1m to 3m. Twenty one (21) points of coal seams was identified using VES at various depths ranging from about 0.9m to 23m. The thickness of the coal seams found in the area ranges from about 0.2m to 4m. The coal in the study area is disseminated and occurred at shallow depth hence it’s not in economic quantity but the coal can be mined locally.